A phase I trial of the trifunctional anti Her2 × anti CD3 antibody ertumaxomab in patients with advanced solid tumors - Hänse, Nicole; Marmé, Frederik; Haag, Georg Martin (BMC cancer, 2016)
Ertumaxomab (ertu) is a bispecific, trifunctional antibody targeting Her2/neu, CD3 and the Fcγ-receptors I, IIa, and III forming a tri-cell complex between tumor cell, T cell and accessory cells.
Gesehen am 15.01.2019